2022
DOI: 10.3928/23258160-20211213-02
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Prevention of Retinal Detachments in Patients with Stickler Syndrome

Abstract: BACKGROUND AND OBJECTIVE: To report the impact of prophylactic laser retinopexy in the prevention of retinal detachments (RDs) in patients with Stickler syndrome. PATIENTS AND METHODS: This was a retrospective, comparative case series of patients with Stickler syndrome from the year 2000 to 2019. We compared the rate of RDs between individuals who did and did not receive prophylactic laser therapy. In patients with an RD, we compared the rate of RD in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Many reports of encircling laser prophylaxis give little description of technique. 4 , 5 , 36 , 37 But its safety and effectiveness can be quite technique dependent. We plan to publish a comprehensive description of optimal technique in a sequel to this article.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many reports of encircling laser prophylaxis give little description of technique. 4 , 5 , 36 , 37 But its safety and effectiveness can be quite technique dependent. We plan to publish a comprehensive description of optimal technique in a sequel to this article.…”
Section: Discussionmentioning
confidence: 99%
“…3,33 Naravane et al and Khanna et al subsequently reported similarly large reductions in RRD rates in (predominately clinically diagnosed) SS, in larger series, using a form of encircling laser retinopexy extending to approximately the equator (26.7% vs 4.6%, p = 0.034; 73% vs 3%, p = 0.001, respectively). 4,5 Linton et al recently reported a fourth encircling laser prophylaxis study for (predominately genetically confirmed) SS, confining treatment to the ora region as a GRT prophylaxis. 34 RRD was reduced from 23% to 9% (p = 0.057), with no GRT lesions seen in the eyes that detached 4318 despite prophylaxis (vs 42.9% GRT in control eyes detaching).…”
Section: Strong Evidence From Stickler Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, two additional studies evaluating laser retinopexy were published. The first retrospective case series examined a cohort of 95 eyes from 48 patients and found that the retinal detachment rate was 26.7% among eyes without previous prophylactic laser retinopexy and only 4.6% among eyes with previous prophylactic laser retinopexy [25]. Laser burns of approximately 500 microns applied with a power titrated to a gray-white color in a nearly confluent pattern of 7-10 rows from the ora serrata for 360 degrees was performed in one session (Figure 1).…”
Section: Laser Retinopexymentioning
confidence: 99%
“…Regarding other usual problems, a total of 40–80% of patients with SS develop retinal detachments and tears. However, these alterations are corrected using prophylactic laser treatment, which was shown to be effective in the treatment of these disorders [ 12 ].…”
Section: Introductionmentioning
confidence: 99%